Non-bank and bank-led electronic banking policy: a comparative study between Kenya and South Africa - Mbhele, Sabelo (My University, 2021)
The research study investigated the impact of electronic banking policy on the adoption and use of payment services offered by bank and non-bank institutions. Using the framework analysis proposed by Srivastava and Thomson (2009), the study employed the unified theory of acceptance and use of technology (UTAUT) as a thematic framework. Based on available research studies, three variables that are prominent in literature, within the financial services context, were identified. The variables are cost, an element of performance expectancy; ubiquity, elements of effort expectancy; and, the operating environment, termed facilitating conditions in the model. The study assessed the performance of banks and non-banks across these variables using published data and relevant research studies. The findings suggest that regulations in the payments industry, and in some respects the lack thereof, potentially had a negative effect on the adoption of non-bank offerings in South Africa. In contrast, the fairly accommodative regulatory approach of Kenyan regulators created a conducive environment for innovation and competition, resulting in increased adoption and usage amongst consumers, with a positive impact on financial inclusion. Most important is perhaps the observed increase in usage as a result of new innovations. This suggests that these innovations have brought about an improvement in the financial welfare of consumers
A research report submitted to the Wits Business School, at the Faculty of Commerce, Law and Management, University of Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in Finance and Investment), 2021
Keywords: Electronic banking policy; Bank and non-bank institutions; Cost; Ubiquity; Operating environment; SDG-8: Decent work and economic growth